The use of olive cake by-product in ruminant diets - Tzamaloukas, Ouranios; Neofytou, M. C.; Simitzis, Panagiotis E; Sparaggis, Dionysis; Miltiadou, Despoina (My University, 2021)
The Mediterranean countries produce the 98% of olive oil worldwide and generate large quantities of olive byproducts that could be considered as alternative feedstuffs with the intention to reduce both the feeding costs and the environmental impacts associated with waste accumulation. Among these by-products, olive cake (OC) is the most abundant containing nutrients and bioactive compounds that vary according to the cultivation conditions (geographic origin, year, season), the process of oil extraction (three or two phase centrifugation), or form and preservation method (crude, partly-destoned, dried or ensiled). With regards to nutrition, OC has a high fibre content, an attribute that makes its inclusion in ruminant diets as a replacement of forages, particularly useful in areas with roughage scarcity. However, its low protein and energy content, or the seasonal availability, possible rancidity and the need for processing may hinder its regular application. In the present review, data from the literature will be presented from earlier and recent studies conducted in ruminants evaluating the effects of various forms of processed OC on milk yield and composition as well as on the lipid profile of meat, milk and dairy products. Then, the proposed underline mechanisms of OC effects on intake, ruminal fermentation, metabolism and milk and dairy products quality will be discussed, suggesting possible ways of this by-product utilisation in ruminant diets.
Keywords: Animal Science; Animal Production